Biallelic loss of FAM46C triggers tumor growth with concomitant activation of Akt signaling in multiple myeloma cells. Issue 5 (9th April 2020) - Kanasugi, Jo; Hanamura, Ichiro; Ota, Akinobu; Karnan, Sivasundaram; Lam, Vu Quang; Mizuno, Shohei; Wahiduzzaman, Md; Rahman, Md Lutfur; Hyodo, Toshinori; Konishi, Hiroyuki; Tsuzuki, Shinobu; Hosokawa, Yoshitaka; et al.
Abstract: Loss of heterozygosity or mutation of the family with sequence similarity 46, member C ( FAM46C ) gene on chromosome band 1p12 is associated with shorter overall survival of patients with multiple myeloma (MM). In this study, using human MM cell lines (KMS‐11, OCI‐My5, and ANBL‐6), we generated FAM46C −/− cell clones and examined the effect of disruption of FAM46C on cell survival and cellular signaling. Cell proliferation assays showed increased clonogenicity of FAM46C −/− KMS‐11 cells compared to WT cells. Xenograft experiments showed significantly shorter overall survival of mice harboring the FAM46C −/− cell‐derived tumors than mice with the FAM46C WT cell‐derived tumors. Notably, levels of phosphorylated Akt and its substrates increased both in vitro and in vivo in the FAM46C −/− cells compared to WT cells. In addition, caspase activities decreased in the FAM46C −/− cells. Results of gene set enrichment analysis showed that loss of FAM46C significantly activated serum‐responsive genes while inactivating phosphatase and tensin homolog (PTEN)‐related genes. Mechanistically, loss of FAM46C decreased the PTEN activity, number of apoptotic cells, and caspase activities. PF‐04691502, a selective PI3K inhibitor, suppressed the augmented phosphorylation of Akt and its substrate FoxO3a. Treatment with afuresertib (a specific Akt inhibitor) in combination with bortezomib additively decreased FAM46C −/− MM cell survival. Collectively, this study is the first to report that loss of FAM46C triggers the concomitant activation of the PI3K‐Akt signaling pathway, which might be a therapeutic target for MM with abnormalities in the FAM46C gene. Abstract : This study shows, for the first time, that FAM46C loss promotes the PI3K‐Akt signaling pathway in multiple myeloma cells. Notably, loss of FAM46C sensitized cells to specific inhibitor of PI3K‐Akt, afuresertib.